Neural and integrative animal physiology. - Prosser, C. Ladd (ed.) (Wiley-Liss Inc., 1991)
"Comparative animal physiology, fourth edition." "This book, Neural and integrative animal physiology, and its companion volume, Environmental and metabolic animal physiology, together comprise the fourth edition of Comparative animal physiology"--Pref.